STUDIES ON THE ASSOCIATION OF A NEW NEMATODE SPECIES SCHISTONCHUS OSMANI SP.N. (APHLENCHOIDEA NICKLE, 1971), A WASP AND FIG FICUS RECEMOSA - RAJESHWARIANAND, L. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
Association of an aphelenchoid nematode Schistonchus osmani n. sp. (Aphelechoidea Nickle, 1971)with a fig pollinating wasp in the fig Ficus recemosa is reported. S. Osmani differs with other species of the genus in the shape of spicules, gubernaculum and male tail.